Peningkatan Kepercayaan Diri Siswa Madrasah Aliyah melalui Pemanfaatan Canva dalam Pelatihan Teknik Presentasi “From Nervous to Confident” - Enny Diah Astuti; Dyan Yuliana; Retno Setya Budiasningrum; Rahmi Rosita; Ali Satri Efendi; Jajang Setiawan (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2026)
Presentation skills and self-confidence are important competencies for students in the digital era, as they support effective communication, creativity, and academic performance. However, many Madrasah Aliyah (MA) students still experience difficulties in expressing their ideas clearly due to nervousness, limited public speaking experience, and inadequate mastery of digital presentation tools. This community service program aimed to enhance students’ presentation skills and self-confidence through digital-based training using the Canva application in the “From Nervous to Confident” program. The program was implemented through several stages, including the delivery of theoretical materials, hands-on training in designing presentation slides with Canva, presentation practice sessions, and constructive feedback from facilitators. The results indicated significant improvements in students’ ability to create visually appealing and well-structured presentation materials. In addition, participants demonstrated greater confidence and improved communication skills when presenting their ideas. Therefore, Canva proved to be an effective learning medium for fostering students’ presentation competence and self-confidence in educational settings.